2013 Canadian Historical Association Presidential Address: On Local History and Local Historical Knowledge / Discours présidentiel 2013 de la Société historique du Canada : de l’histoire locale et de la connaissance locale du passé - Dick, Lyle (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2013)
This article considers two undervalued aspects of historical production — local history and local historical knowledge. It distinguishes between microhistory as carried out by professionals and local history as practised by vernacular historians, sometimes in collaboration with professionals. Relating his own experience with the genre of local history, the author highlights the importance of local historical knowledge as held and transmitted by community elders. His collaboration with the Elders of the Inuit community of Grise Fiord, Nunavut, is discussed as an illustration of its potential. The collaborative and dialogical character of local historical knowledge is further exemplified by folklorist Henry Glassie’s work with a small Northern Irish community. Noting current challenges of changing demographics, uprootedness and diaspora, the article considers how emerging communities and minorities are recreating new opportunities for local historical knowledge in Canada’s cities. Heeding the advice of senior Elders such as the late William Commanda of the Algonquin First Nation at Maniwaki, Quebec, the author asserts the importance of local historical knowledge to Canadians’ identities as members of communities with a common history, strengthening connections between people, past and present, and positioning us to better face the future.